An anthropometric study to develop clothing charts for seventh, eighth and ninth grades of Benghazi schoolchildren - Bilhassan, S. A.; Albarki, F.; Bu-Hager, A.; Basheer, M.; Ali, M. (Libyan Journal of Science &Technology, 2022)
A sizing system classifies a specific population into homogeneous subgroups based on some key body dimensions. Individuals in the same subgroup have the same body shape characteristics, and share the same garment size. Anthropometric data plays an important role in creating clothing sizing system. The current project is the third step towards the overall objective to develop a clothing sizing system for Libyan children based on anthropometric body measurements of Libyan schoolchildren. The aim of the current project is to collect, examine and analyze anthropometric measurements for students in grades seven, eight and nine in the basic education stage, using simple statistical methods, in order to understand the body ranges and variations to develop sizing system for these grades. ANOVA tests were used to identify differences between age groups. The results showed that there are differences between most of the body measurements except the waist circumference, chest circumference, arm circumference, elbow circumference, shoulder length, front body width and back body width. Pearson correlation coefficients analysis was carried out to determine the interrelationships between the various body measurements. These findings showed that the weight and waist circumference were very strongly correlated with some other dimensions. The mean values and the standard deviation were used for creating size steps for the size chart. Three kinds of sizes were identified: L (large), M (medium) and S (small).